Reversal of visceral hypersensitivity in rat by Menthacarin®, a proprietary combination of essential oils from peppermint and caraway, coincides with mycobiome modulation. Issue 6 (31st January 2018) - Botschuijver, S.; Welting, O.; Levin, E.; Maria‐Ferreira, D.; Koch, E.; Montijn, R. C.; Seppen, J.; Hakvoort, T. B. M.; Schuren, F. H. J.; de Jonge, W. J.; van den Wijngaard, R. M.
Abstract: Background: Irritable bowel syndrome (IBS) is a common gastrointestinal disorder associated with altered gastrointestinal microflora and increased nociception to colonic distension. This visceral hypersensitivity can be reversed in our rat maternal separation model by fungicides. Menthacarin ® is a proprietary combination of essential oils from Mentha x piperita L. and Carum carvi . Because these oils exhibit antifungal and antibacterial properties, we investigated whether Menthacarin ® can reverse existing visceral hypersensitivity in maternally separated rats. Methods: In non‐handled and maternally separated rats, we used the visceromotor responses to colorectal distension as measure for visceral sensitivity. We evaluated this response before and 24 hours after water‐avoidance stress and after 7 days treatment with Menthacarin ® or control. The pre‐ and post‐treatment mycobiome and microbiome were characterized by sequencing of fungal internal transcribed spacer 1 (ITS‐1) and bacterial 16s rDNA regions. In vitro antifungal and antimicrobial properties of Menthacarin ® were studied with radial diffusion assay. Key Results: Menthacarin ® inhibited in vitro growth of yeast and bacteria. Water‐avoidance caused visceral hypersensitivity in maternally separated rats, and this was reversed by treatment. Multivariate analyses of ITS‐1 and 16S high throughput data showed that maternal separation, induced changes in the myco‐ and microbiome. Menthacarin ® treatment of non‐handled and maternally separated rats shifted the mycobiomes to more similar compositions. Conclusions & Inferences: The development of visceral hypersensitivity in maternally separated rats and the Menthacarin ® ‐mediated reversal of hypersensitivity is associated with changes in the mycobiome. Therefore, Menthacarin ® may be a safe and effective treatment option that should be tested for IBS. Abstract : The gut fungal microbiome (mycobiome) was recently identified as a possible cause for abdominal pain in IBS. We showed that a peppermint‐ and caraway‐oil‐preparation with fungicidal activity, called Menthacarin ®, can reverse mycobiome‐dependent visceral hypersensitivity in rat.